PENGARUH INTENSITAS CAHAYA MATAHARI DANKETERSEDIAAN AIR TERHADAP PERTUMBUHANTANAMAN CABAI RAWIT (Capsicum frutescens L.) - Ajis Ajis; Wahyu Harso (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Light intensity is one the most important factor to the growth of Capsicum frutescens L, however high light intensity can cause high evaporation which causes plant suffering from drought. The aim of this study was to determine the effect of different sunlight intensities and soilwater availabity to C. frutescens growth. The study was conducted by a completely randomized design method with two factors. The first factor was light entensity which consisted of 100 and 50% sunlight intensity (4287 and 2587 lux). The second factor was soil water avaibility which consisted of 75, 50 and 25% fied capacity. The results showed that plants grown at 100% light intensity had higher growth than plants grown at 50% light intensity on every soil water availability treatments. Soil water availability was not significantly affecting plant growth. It might be caused by plant received short period of sunlight.